Sub chronic toxicity asssay of aqueous extract of the leaves of Nerium indicum Mill. on male white mice (Ratus norvegicus) strain wistar - Prasetyawati, Citra; Argo D, Imono; Hartati W, Mae Sri; Wahyuono, Subagus (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Aqueous extract of the leaves of Nerium indicum Mill. is traditionally used to treat cancer. The extract has been consumed for relatively a long time, consequently major organs are often intoxicated. Therefore, this study was aimed to determine sub chronic toxicity of the aqueous extract on male mice. Toxic symptoms, major organs intoxicated and haematological changes due to treatment of aqueous extract of the leaves of N. indicum are determined.Twenty male mice (185-250 g, strain wistar) are divided into 4 groups [I, treated with aquadest (3 ml/200 g BW); II, treated with water extract (5%, 3ml/200 g BB); III, treated with water extract (10%, 3 ml/200 g BB); and IV, treated with water extract (20%, 3 ml/200 g BB)]. Toxic symptoms are observed after 3 hours of treatment; body weight, haematological measurement, food intake, urine chemistry, SGPT, ureum, and histopathological pictures are also observed. The results of the study do not show any toxic symptoms, the body weight and food intake of the mice increase (I-IV). There are no major organs intoxicated; however a slight increase of leukocyte (WBC, white blood cell) count is clearly showed by group IV.It is concluded that consuming aqueous extract (20%, the highest concentration) of N. indicum for 30 days does not elicit toxic effect in mice. Any changes occur are still at the normal range.Keywords: Nerium indicum Mill., water extract, toxicity, sub chronic